2021
DOI: 10.4236/jcc.2021.95005
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Frequency Interference Detection and Mitigation Using Multiple Adaptive IIR Notch Filter with Lattice Structure

Abstract: Radio Frequency Interferences (RFI), such as strong Continuous Wave Interferences (CWI), can influence the Quality of Service (QoS) of communications, increasing the Bit Error Rate (BER) and decreasing the Signal-to-Noise Ratio (SNR) in any wireless transmission, including in a Digital Video Broadcasting (DVB-S2) receiver. Therefore, this paper presents an algorithm for detecting and mitigating a Multi-tone Continuous Wave Interference (MCWI) using a Multiple Adaptive Notch Filter (MANF), based on the lattice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…These approaches totally eliminate jamming, but they generate a self-noise, which causes distortion and loss of some useful signals. To limit the loss and distortion of useful signals while eliminating jamming, we present a low-complexity algorithm approach for both direct and lattice IIR NF forms structure based on a second-order NF to mitigate CW and MCW interferences and adjust notch depth and compare between two structures, which has not been studied in previous works-particularly [18] [36] [37] [38]. Furthermore, based on the comparison of the two structures and the results derived by MATLAB® Simulation, we observed that the lattice IIR NF structure achieves better performance than the direct IIR NF structure for detecting and removing jamming.…”
Section: Simulation Results For Performance Comparison and Discussionmentioning
confidence: 99%
“…These approaches totally eliminate jamming, but they generate a self-noise, which causes distortion and loss of some useful signals. To limit the loss and distortion of useful signals while eliminating jamming, we present a low-complexity algorithm approach for both direct and lattice IIR NF forms structure based on a second-order NF to mitigate CW and MCW interferences and adjust notch depth and compare between two structures, which has not been studied in previous works-particularly [18] [36] [37] [38]. Furthermore, based on the comparison of the two structures and the results derived by MATLAB® Simulation, we observed that the lattice IIR NF structure achieves better performance than the direct IIR NF structure for detecting and removing jamming.…”
Section: Simulation Results For Performance Comparison and Discussionmentioning
confidence: 99%
“…In GPS, ref. [42] proposed a method to mitigate CWI using adaptive FIR and ACM filters, while [43] proposed a method based on the lattice-form structure for detecting and mitigating an MCWI by controlling the depth of the NF.…”
Section: Related Workmentioning
confidence: 99%
“…To reduce and mitigate CWI, [41] presented a new low-complexity anti-jamming NF for general wireless communications, while [42] derived FIR excision filters that optimize receiver SNR for NB interference. In GPS, [42] proposed a method to mitigate CWI using adaptive FIR and ACM filters, while [43] proposed a method based on the lattice-form structure for detecting and mitigating an MCWI by controlling the depth of the NF.…”
Section: Signal Modelmentioning
confidence: 99%